Effect of powder loading on plasma spheroidization of hydride-dehydride titanium powders. (8th October 2021) - Kambara, M.; Fukuda, M.; Ohta, R.; Tanaka, T.; Takeuchi, A.; Dougakiuchi, M.; Fukuda, K.
Abstract: Spherical titanium particles have been produced from hydride-dehydride titanium raw powders using an inductively coupled plasma spray system. Taking into account the variously modified particle morphologies with different plasma conditions, the effect of powder loading on spheroidization was quantified and evaluated in terms of the altered particle heating capabilities. The averaged particle heat transfer coefficient was found to vary with powder feeding rate and associated strongly with Ar–H2 gas thermal conductivity. Furthermore, there observed a most efficient particle heating condition for each powder feeding rate, but the efficient heating condition tends to vaporize small raw powders and increase the overall oxygen content unintentionally as a result of the attachment of satellites nanoparticles on spherical particles. It is therefore important that the plasma input power is optimally controlled with particular attention to the altered degree of heat transfer especially for the case of small powder injection.